A sufficient condition for fractional ID-[a, 6]-factor-critical covered graphs - Jiang, Jiashang (Utilitas Mathematica, 2020)
A graph G is fractional ID-[o, 6)-factor-critical covered if for any independent set I of G, G-I is fractional [o, 6]-covered. In this article, we present a neighborhood union condition for a graph to be fractional ID-[a,6]-factor-critical covered, and show this result is best possible in some sense. © 2020 Utilitas Mathematica Publishing Inc.. All rights reserved.